Effectiveness of Cognitive Mindfulness-based-Therapy on Resilience and Emotional Control of Psychiatric Veteran's Wives - V. Mozaffari (Afarand Scholarly Publishing Institute, 2019)
Aims: Psychiatric veterans' wives are exposed to psychological damages due to their husbands' specific condition. The aim of the present study was to investigate the effectiveness of cognitive mindfulness-based-therapy on resilience and emotional control of psychiatric veteran's wives. Materials and Methods:  The present study was a semi-experimental design with a pretest, post-test design with a control group conducted in Tehran in 2017. In order to conduct this research, a sample of 30 people from the research population (psychiatric veteran's wives in Tehran) were selected, using available sampling method and were randomly selected in experimental and control groups. The instruments included the resilience and emotional control questionnaires. Before administering the independent variable the pretest was taken from both groups. Then, the experimental group received teaching intervention during 8 sessions in 2-and-a-half month period. Shapiro-Wilk test, Levenechr('39')s test, and univariate covariance analysis as well as SPSS 23 were used to analyze the data. Findings: Cognitive mindfulness-based-therapy significantly affected resilience and emotional control of psychiatric veteran's wives (p<0.05) in such a way that this treatment could significantly improve the resilience and emotional control in psychiatric veteran's wives. Conclusion: Cognitive mindfulness-based-therapy can improve resilience and emotional control of psychiatric veterans' wives, and regarding this effect, this treatment can be used to improve their resilience and emotional control.